The crown of embers - Carson, Rae (Carson, Rae. Girl of fire and thorns trilogy., 2012)
"Hero. Foreigner. Queen. Elisa, at the age of seventeen, is all three. And all three draw enemies. Faced with assassins, court politics, and the threat of civil war, Elisa despairs of being the ruler her people need. Her only hope is the Godstone. She must master its power once and for all. She finds clues hidden in a long forgotten--and forbidden--scripture. Accompanied by a one-eyed warrior, an enemy defector, and the man she is falling in love with, Elisa takes a leap of faith and crosses an ocean in search of the ultimate source of the Godstone's power. But her faith has always had a price, and doing the right thing might mean giving up the power she desperately needs. And it might mean giving up the man she desperately loves. Rae Carson continues the epic story begun in The Girl of Fire and Thorns with a novel that is remarkable, adventurous, and even more romantic than the first"--